Reductive sequestration of chromate by hierarchical FeS@Fe(0) particles - Du, Jiangkun; Bao, Jianguo; Lu, Chenghang; Werner, David (Water research (Oxford), 2016)
Nanoscale Fe(0) (nFe(0)) can detoxify Cr(VI)-bearing wastewater and groundwater, but rapid passivation is a negative factor for large-scale remediation applications. In this study, a magnetic FeS@Fe(0) hybrid material was fabricated by immobilization of iron sulfide (FeS) onto Fe(0) particles to improve the Cr(VI) removal capacity. The solid characterization confirmed that Fe(0) particles were encapsulated by amorphous iron monosulfide. The Cr(VI) uptake by FeS@Fe(0) hybrid particles was found to follow pseudo-second-order rate kinetics, and the Langmuir isotherm was most appropriate to describe Cr(VI) sorption. Meanwhile, the FeS@Fe(0) hybrid particles showed a much higher efficiency towards Cr(VI) sequestration compared to individual nFe(0). Moreover, the results of batch experiments with various adsorbent doses indicated that the reactivity of FeS@Fe(0) varies with different FeS-to-Fe(0) molar ratios. The reaction rate constants for Cr(VI) removal first increased with an increasing FeS-to-Fe(0) ratio from 0/1 to 1/9, and then decreased for the FeS-to-Fe(0) ratio increased further 1/5 or 1/3. For environmental parameters, there was a negative effect of increasing the solution pH and dissolved oxygen on Cr(VI) removal. Furthermore, a mechanistic analysis revealed that Cr(VI) reduction occurred predominantly at the solid-liquid interface, and that Fe(II) regenerated from FeS@Fe(0) corrosion may account for 52% of the Cr(VI) reduction, while electrons from Fe(0) and FeS account for the rest. After treatment, Cr(VI) was completely transformed and immobilized as solid Fe-Cr hydroxide precipitates, thus avoiding secondary contamination. The FeS@Fe(0) hybrid material has a better potential for treating Cr(VI)-bearing wastewater than nano Fe(0).